Classification of Choroiditis Based on Inflammatory Lesion Process rather than Fundus Appearance: Enhanced Comprehension through the ICGA Concepts of the Iceberg and Jellyfish Effects - Herbort, C. P.; Papadia, M.; Mantovani, A. (Klinische Monatsblätter für Augenheilkunde, 2012)
Choroidal inflammatory diseases have been classically grouped under the term of white dot syndromes (WDS), a term only based on the appearance (white-yellow dots) of inflammatory fundus lesions. This purely descriptive and vague terminology, regrouping a pot-pourri of posterior inflammatory conditions, probably came into use because the precise exploration of the choroid was not possible, and also because many of the diseases were rare and not well understood. Since the availability of indocyanine green angiography (ICGA) that allows one to explore the choroidal compartment, it became possible to understand the lesion mechanism of choroiditides and to classify this group of diseases according to their pathophysiological behaviour. It was our aim to show here that the term WDS is applied to and encompasses inflammatory conditions that are characterized by completely different lesion mechanisms and should therefore be classified separately from each other. ICGA made it possible to differentiate two types of choroiditides, including on the one hand inflammatory diseases of the choroidal stroma and on the other hand inflammatory diseases of the choriocapillaris. Unfortunately, twenty years after its advent, ICGA is still not used routinely in uveitis centres and the traditional inappropriate but overall useless term of WDS is still used, maintaining the confusion about these diseases. The aim of this work was (i) to illustrate that meaningful exploration of choroidal inflammation, mostly occult and inaccessible to usual investigations, has to be performed using ICGA, (ii) to insist on the crucial importance of ICGA in the management of choroiditis and (iii) to enhance the comprehension of the ICGA-based classification of choroiditis, by using the demonstrative and striking analogue concepts of iceberg and jellyfish effects.
Keywords: choroiditis; indocyanine green angiography (ICGA); stromal choroiditis; choriocapillaritis; iceberg effect; jellyfish effect; white dot syndromes